Myelin Oligodendrocyte Glycoprotein Antibody Associated Transverse Myelitis - Chroustová, Iveta; Mareš, Miroslav; Ungermann, Leoš; Ehler, Edvard (Karolinum, 2019)
Antibodies against myelin oligodendrocyte glycoprotein cause inflammatory lesions of central myelin – in optic nerves, of the brainstem, and spinal cord. There are characteristic changes of CNS white matter, protein-cytological association in cerebrospinal fluid, MOG IgG antibodies, a very important differential diagnosis and a relatively mild course.
Protilátka proti myelin oligodendrocyte glycoprotein (MOG) sdružená s transverzní myelitidou
Keywords: myelin oligodendrocyte glycoprotein; inflammation; spinal cord; antibodies; Myelin oligodendrocyte glycoprotein,zánět,mícha,protilátky